A survey of perceived training differences between ophthalmology residents in Hong Kong and China. Issue 1 (December 2015) - Young, Alvin; Jhanji, Vishal; Liang, Yuanbo; Congdon, Nathan; Chow, Simon; Wang, Fenghua; Zhang, Xiujuan; Man, Xiaofei; Yang, Mingming; Lin, Zhong; Yuen, Hunter; Lam, Dennis
Abstract Background To study the differences in ophthalmology resident training between China and the Hong Kong Special Administrative Region (HKSAR). Methods Training programs were selected from among the largest and best-known teaching hospitals. Ophthalmology residents were sent an anonymous 48-item questionnaire by mail. Work satisfaction, time allocation between training activities and volume of surgery performed were determined. Results 50/75 residents (66.7 %) from China and 20/26 (76.9 %) from HKSAR completed the survey. Age (28.9 ± 2.5 vs. 30.2 ± 2.9 years, p  = 0.15) and number of years in training (3.4 ± 1.6 vs. 2.8 ± 1.5, p  = 0.19) were comparable between groups. The number of cataract procedures performed by HKSAR trainees (extra-capsular, median 80.0, quartile range: 30.0, 100.0; phacoemulsification, median: 20.0, quartile range: 0.0, 100.0) exceeded that for Chinese residents (extra-capsular: median = 0, p  < 0.0001; phacoemulsification: median = 0, p  < 0.0001). Chinese trainees spent more time completing medical charts (>50 % of time on charts: 62.5 % versus 5.3 %, p  < 0.0001) and received less supervision (≥90 % of training supervised: 4.4 % versus 65 %, p  < 0.0001). Chinese residents were more likely to feel underpaid (96.0 % vs. 31.6 %, p < 0.0001) and hoped their children would not practice medicine (69.4 % vs. 5.0 %, p  = 0.0001) compared HKSAR residents. Conclusions In this study, ophthalmology residents in China report strikingly less surgical experience and supervision, and lower satisfaction than HKSAR residents. The HKSAR model of hands-on resident training might be useful in improving the low cataract surgical rate in China.